Public interest in and acceptability of the prospect of risk-stratified screening for breast and prostate cancer. (2nd January 2016) - Koitsalu, Marie; Sprangers, Mirjam A. G.; Eklund, Martin; Czene, Kamila; Hall, Per; Grönberg, Henrik; Brandberg, Yvonne
Abstract : Background. For risk-stratified screening to be implemented as a screening program for breast and prostate cancer it has to be accepted among the general population. Investigating public interest in stratified screening and its acceptability to the public is therefore essential since as yet little is known. Method. Cross-sectional web survey sent to a sample of 10 000 individuals (20–74 years of age) representative of the Swedish population as registered in 2009. Results. Among the responders (28%), a vast majority (94%) expressed an interest in knowing their breast or prostate cancer risk and stated wanting to know to 'avoid worrying'. Men and women were equally interested in knowing their prostate and breast cancer risk, respectively. However, men showed more certainty. Trusting the healthcare workers with personal information (63%) as well as genetic information (70%), in order to calculate the risk, did not seem to be a major issue. Furthermore, 87% would agree to get screened more often if identified with a high risk, whereas, if identified with a low risk, only 27% would agree to get screened less often. Finally, although a consultation with a physician seemed to be the preferred way to communicate the risk, a majority would agree to receive it via a letter or a phone call. Conclusion. Risk-stratified screening has the possibility to be accepted by the general public. Knowledge about interest and acceptability of the prospect of risk-stratified screening for breast and prostate cancer will help when implementing new screening strategies.